SLL-PEEP Ventilation to Improve Exposure in Minimally Invasive Right Anterolateral Minithoracotomy Aortic Valve Replacement. Issue 4 (July 2021) - Richter, Gregor; Van Praet, Karel M.; Hommel, Matthias; Sündermann, Simon H.; Kofler, Markus; Meyer, Alexander; Unbehaun, Axel; Starck, Christoph; Jacobs, Stephan; Falk, Volkmar; Kempfert, Jörg
Objective: An accepted landmark to assess feasibility of surgical aortic valve replacement (SAVR) via right anterolateral minithoracotomy (RALT) is the aortic-midpoint to right-sternal-edge distance. We aimed to evaluate single left lung positive-end-expiratory-pressure (SLL-PEEP) ventilation inducing an intraoperative rightward shift of the ascending aorta to improve exposure. Methods: Nineteen patients with aortic stenosis undergoing SAVR via RALT were prospectively analyzed. SLL-PEEP ventilation (20, 395 cmH2 O) via a double-lumen endotracheal tube was applied immediately before transthoracic aortic cross-clamping, thereby inducing rightward shift of the ascending aorta to enhance exposure. We analyzed preoperative computed tomography (CT) reconstructions and intraoperative video recordings. Primary endpoint was extent of rightward shift induced by SLL-PEEP ventilation; secondary endpoints were procedure times and safety events. Results: Mean age was 61 ± 14.8 years and 6 of 19 (31.6%) were female. Mean EuroSCORE II was 0.81% ± 0.04%, STS-PROM was 1.13% ± 0.74%, and mean aortic rightward shift induced by SLL-PEEP ventilation was 10.32 ± 4.14 mm (4 to 17 mm; P = 0.003). Median shift in the group considered suitable for the RALT approach by preoperative CT-scan evaluation was 14.2 mm (IQR 11) and in the less suitable group 11.5 mm (IQR 5). Mean procedure time was 167 ± 28.9 min, CPB time was 105.7 ± 18.4 min, and cross-clamp time was 64.5 ± 13 min. Fifteen patients (79%) received SAVR via RALT with implantation of a bioprosthesis, whereas a rapid-deployment-prosthesis was used in 4 patients (21%). Ten of 19 (53%) patients who were classified as less suitable preoperatively received SAVR via RALT after SLL-PEEP ventilation. No strokes were observed. Conclusions: The SLL-PEEP ventilation maneuver during SAVR via RALT significantly enhances aortic exposure. There were no safety events associated with this maneuver and we were able to demonstrate significant rightward aortic shift in every single patient.